Performance of an Human Papillomavirus Test in Samples From Women With Histolopathologically Confirmed Invasive Cervical Cancer. Issue 2 (April 2016) - Mbatani, Nomonde; Adams, Tracey; Wijk, Leon van; Behrens, Catherine; Tam, Thanh; Wright, Thomas; Stoler, Mark; Denny, Lynette
Abstract : Background: High-risk human papillomavirus (hrHPV) is now recognized as a single, necessary cause of cancer of the cervix. Although Pap tests have been central to cervical cancer screening programs for more than 50 years, tests that detect infection with these hrHPV genotypes are now being used increasingly in cervical cancer screening programs. Objective: The aim of the study was to determine the sensitivity of an HPV test to detect cervical cancer. Materials and Methods: Fifty successive cervical samples from women diagnosed with invasive cervical cancer were tested using a molecular HPV DNA test. Thereafter, the residual sample was further tested with a different HPV genotyping test (capable of detecting 27 low- and high-risk types of HPV) and a nucleic acid hybridization test (capable of detecting 13 high-risk types of HPV). Results: Of the 50 women tested, the first HPV test was positive in 47 cases. Of the 3 negative cases, all were negative by second polymerase chain reaction–based test and 2 were negative by the nucleic acid hybridization test. Human immunodeficiency virus status was positive in 14 women, the majority of whom were positive for HPV 16 ( n = 8) and 1 was HPV negative. Most women were diagnosed with having stage II cervical cancer or higher. Conclusions: With a sensitivity of 94% of the first HPV test, 6 of 100 cervical cancers will be missed if this was the only test used in a population screening program. The missed cancers were however all clinically detectable. Abstract : HPV has high sensitivity for detection of cervical cancer. Supplemental digital content is available in the text.